REPRODUCTION OF FEATURES OF KOBZAR EXECUTION IN M. LYSENKO'S ROMANCE «ON SUNDAY EARLY IN THE MORNING» - Shevchenko Ruslana (International Journal of Innovative Technologies in Social Science, 2020)
The connections of the composer with kobzars who performed dumas in the period from the end of the XIX to the beginning of the XX century are considered. A comparative analysis of the epic works (dumas) of S. Pasyuga, G. Honcharenko, P. Drevchenko, I. Kucherenko was carried out. They were recorded and edited by F. Kolessa. The piano texture of the romance «On Sunday early in the morning» for the presence of elements of bandura playing has been studied. It is noted that the composer creatively rethought them in the vocal work. By reproducing the performance style of kobzars, M. Lysenko created an imitation of an authentic duma. It is determined that the features of the epic work influenced the form of the vocal work and the organization of the piano texture. M. Lysenko reflected the most typical elements of kobzar performance and the texture of the accompaniment of thoughts. In the romance, the composer recreated the improvisational way of thinking of kobzars. This was reflected in the methods of development of thematic material and the introduction of bandura semantics in the piano part.In the vocal work M. Lysenko created the effect of the sound of a folk instrument. The composer creatively transferred the techniques of kobza`s art to the piano texture of romance. They became part of his musical language. This determined the innovation and uniqueness of M. Lysenko's work.